Recent advances of G protein‐coupled estrogen receptor 1 in the metabolism of bone - FENG Yuan; WANG Zuolin (Kouqiang hemian waike zazhi)
The G protein‐coupled estrogen receptor 1 (GPER1) is a membrane receptor for estrogen and it plays an important role in estrogen mediated bone metabolism by triggering downstream responses through rapid cellular pleiotropic effects and influencing the proliferation and differentiation of osteoblasts. This article provides a brief summary of the role of GPER1 in bone metabolism, including the involvement of GPER1 in bone growth during puberty, the realization of different functions in bone metabolism at different estrogen levels in the body, and the participation in bone metabolism in cooperation with other receptors.